Decoding the core of words: Enhancing vocabulary through listening practice using the ‘Listen a Minute' website. - Salsa Nabila; Aries Fachriza; Dinar Dipta; Diska Fatima Virgiyanti (Journal of English Language Teaching and Learning (JETLE), 2026)
Vocabulary recognition plays a crucial role in identifying key information of spoken text in listening comprehension. This study aligns with Brown’s theory, which posits that listening involves bottom-up processing that requires learners to recognize and interpret sounds, words, and grammatical structures. This study aimed to examine how effectively the Listen A Minute website helped tenth-grade students of Secondary Level at Senior High School in Central Java recognize key words through listening exercises. A quasi-experimental approach with an experimental and control group was employed. The sample consisted of 60 tenth-grade students of Secondary Level at Senior High School in Central Java . The experiment used a material from the Listen A Minute website, while the control group received the conventional listening. Data were collected from pre- and post-test listening assessments, which were analyzed using descriptive statistics and the Mann–Whitney U test. Results revealed a significant difference between the two groups, with a p-value of 0.003 (p 0.05). These findings reject the null hypothesis and support the alternative hypothesis. The findings indicated that students’ ability to identify keywords during listening tasks significantly improved when using the Listen A Minute website. Therefore, the website can be considered an effective pedagogical tool for improving listening comprehension, particularly in identifying key information in spoken texts.